Prevalence and predictors of developing vision-threatening diabetic retinopathy within the first three years of type 2 diabetes - Yan, Jia; Li, Bo; Chen, Ye; Gu, Chufeng; Dai, Guosheng; Zhang, Qin; Zheng, Zhi; Luo, Dawei; Zhao, Shuzhi; Zhou, Chuandi (Frontiers in Endocrinology, 2023)
Purpose To investigate the prevalence of diabetic retinopathy (DR) and vision-threatening DR (VTDR) in patients with type 2 diabetes mellitus (T2DM) stratified by the duration of diabetes, and further to identify the clinical variations and risk factors for VTDR occurred in different stages of T2DM. Methods A retrospective comparative study. Patients were divided into short-(≤3 years), intermediate-(3-7 years), and long-(>7 years) duration groups. All patients were followed up for the development DR and VTDR. Risk factors were explored by logistic regression.Results A total of 2961 patients were included, among them, 1036(35.0%) patients developed DR, and 293(9.9%) had VTDR. The frequency of VTDR in patients who developed DR of short-duration group was significantly higher than that of intermediate-duration group (25.7% vs 15.0%; p=0.019) but comparable with that of long-duration group (25.7% vs 31.8%; p=0.138). The patients developed VTDR within the first 3 years of T2DM were more likely to have a family history of diabetes (p=0.024), higher glycated hemoglobin (p=0.025), be males (p=0.042), and were notably older at the onset of diabetes (p<0.001) but younger when diagnosed with DR (p<0.001). Moreover, higher glycated hemoglobin (OR=1.14; 95% CI: 1.00-1.29; p=0.043) and diabetic nephropathy (DN) (OR=2.31; 95% CI: 1.08-4.91; p=0.030) were independent risk factors for developing VTDR during the first 3 years of T2DM.The risk of having DR is not high in persons with ≤3 years' duration of T2DM, however, if afflicted, the risk of VTDR should never be neglected. More frequent retinal screenings are warranted for patients with newly diagnosed T2DM.